2010
DOI: 10.1007/s10661-010-1849-x
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticide (OCP) residues in cow’s, buffalo’s, and sheep’s milk from Afyonkarahisar region, Turkey

Abstract: In this study, it was aimed to determine organochlorine pesticides (OCPs) in three types of milk (cow's, buffalo's, and sheep's milk) produced in Afyonkarahisar province of Turkey. The results indicated that these milk specimens were found to be contaminated by 21 different pesticides. Sixteen OCP residues were detected in sheep's milk and it was followed with 14 pesticides in buffalo's milk and 11 pesticides in cow's milk. Dominant pesticides in all samples examined were beta-HCH in buffalo's, cow's, and shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…However, the frequency of HCB-positive samples in the current investigation was lower than those detected by Campoy et al (2001) and Heck et al (2007), who reported positive frequencies of 94-100% and 100%, respectively, with a mean concentration of 0.003 mg/kg. In more recent study in Turkey, our values resembled those measured by Bulut et al (2011).…”
Section: Discussionsupporting
confidence: 88%
“…However, the frequency of HCB-positive samples in the current investigation was lower than those detected by Campoy et al (2001) and Heck et al (2007), who reported positive frequencies of 94-100% and 100%, respectively, with a mean concentration of 0.003 mg/kg. In more recent study in Turkey, our values resembled those measured by Bulut et al (2011).…”
Section: Discussionsupporting
confidence: 88%
“…In Turkey, Bulut et al (2011) investigated the contamination status of 50 milk samples of water buffaloes by OCPs from Afyonkarahisar region. They found beta-HCH levels above the MRL established in EC regulation and reported that the incidence were 64%, 16%, 8%, 6% and 2% for beta-HCH, 4,4'-DDT, Aldrin, gamma-HCH and delta-HCH, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Güvenç and Aksoy () analyzed 100 samples of cows’ milk collected from Samsun region in terms of nine organochlorines and five synthetic pyrethroids pesticides and did not find any pesticide residues in any of their samples. On the other hand, Bulut, Akkaya, Gök, and Konuk ( and ) found that in butter samples consumed in Afyon, there was 0.002 mg/kg fat α‐HCH, 0.214 mg/kg fat β‐HCH, 0.003 mg/kg fat γ‐HCH, 0.005 mg/kg fat p,p 1 ‐DDE, and 0.025 mg/kg fat p,p 1 ‐DDT; in cream samples there was 0.001 mg/kg fat α‐HCH, 0.09 mg/kg fat β‐HCH, 0.004 mg/kg fat γ‐HCH, 0.007 mg/kg fat p,p 1 ‐DDE, and 0.019 mg/kg fat p,p 1 ‐DDT; in milk samples there was 0.091 mg/kg fat β‐HCH and 0.016 mg/kg fat p,p 1 ‐DDT.…”
Section: Resultsmentioning
confidence: 99%